The white nipple sign. Issue 3 (21st May 2012) - Kasturi, Rangarajan; Patodi, Nishant; Ahmed, Mohammed Monzur; Lim, Chee
Abstract : The white nipple sign is a term used to describe a fresh fibrin clot on a varix that has bled recently. The authors describe a case to highlight the importance of prompt endo-therapy when this sign is recognised as disturbing this clot can cause brisk bleeding